Performa Estrus dan Hormon Estrogen Sapi Friesian Holstein Postpartus yang Diberi Urea Multinutrient Molasses Block (UMMB) dengan Perekat Tepung Tapioka - Hasbi, Hasbi; Ramadan, Zyahrul; Utamy, Renny Fatmyah; Ako, Ambo; Masturi, Masturi; Gustina, Sri; Tasya, Tasya; Mufliha, Rara; Nurbina, Andi Fitri; Mutfaidah, Andi; Saputra, Rio; Mahayani, I Dewa Ayu; Mutmainna, Mutmainna; Rahman, Andi Arif; Sukri, Siti Annisa (Jurnal Sain Veteriner, 2024)
The reproductive ability of Holstein Friesian (FH) cows greatly affects milk yield because, however, in the lactation period, dairy cows anestrus postpartus, which is the condition where does not appear in estrus postpartus. Anestrus postpartus to uterine involution as a consequence of nutritional deficiencies. Recovery from can be this condition can be conducted by additional feeding. One of the supplementary feeds is urea multinutrient molasses block (UMMB). UMMB consists of fillers and adhesives and cement is the most used in UMMB production as an adhesive. UMMB is an additional feed using cement dairy cows health problems. Therefore, the objective of this research was to determine the effect of cement substitution with tapioca meal as an adhesive on postpartus estrus of FH cows. A total of 9 lactating FH dairy cows were divided into 3 dietary groups. Each treatment had 3 cows as replicates. The dietary treatments consisted of UMMB with 100% cement adhesive (as D0); 50% cement and 50% tapioca (D1); and 0% cement and 100% tapioca meal (D2). The parameters were postpartus estrus, estrus speed, estrus duration, estrus intensity, and estrogen hormone levels. The results revealed that the treatment had a significant effect (P<0.05) on the duration of estrus, while it had no significant effect (P>0.05) neither on postpartus estrus, estrus speed, estrus intensity, or estrogen hormone levels. Therefore, it can be concluded that tapioca meals can be used as a substitute for cement as much as 50% provides as an adhesive in UMMB production for better estrus performance.